Father of the bride - Shyer, Charles (Quezon City : Viva Video, 2003)
In this hilarious, crowd-pleasing sequel to the comedy smash Father of Bride, you can expect Steve Martin (Parenthood) and Diane Keaton (Baby Boom) to deliver big laughs and a great time! George Bank (Martin) Feels far too young to be grandfather... and way too old to become a father again. So when his recently married daughter Annie and his wife Nina (Keaton) both announce they're pregnant, the news send George headlong into a wacky mid-life crisis as she desperately tries to recapture his youth. But the fun only doubles as the Banks household then gets turned completely upside-down by partly planner extraordinaire Frank Egglehoffer (Martin Short), who returns to throw the baby shower of the country just as everyone is anxiously awaiting the delightful double delivery.